The performances of Islamic unit trust industry: The case of principal assets management bhd - Jamsari, Samad (2023)
Unit trust advisors face various challenges that impact their performance and these challenges can significantly hinder their abilities to meet targets and deliver optimal result. Therefore, understanding the unit trust industry's performance is vital for unit trust companies to provide the necessary supports and resources to their advisors. The study aims to analyze impacts of role perception, knowledge & skills, motivation, personal characteristics, aptitude, organizational variables on unit trust advisor performances. It seeks to determine the impact of these variables on the overall performances of unit trust advisors in meeting client needs and achieving investment objectives. Furthermore, the study examines the issues that unit trust advisors encounter, shedding light on challenges that hinder their abilities to deliver optimal results. This study adopts a qualitative approach, utilizing in-depth interviews with 12 unit trust advisors and managerial personnel to gather rich and nuanced insights. The findings underscore the intricate nature of advisor performance, revealing that multiple factors converge to shape unit trust advisor performances. Notably, their performance influenced by market conditions, emerges as a critical determinant of advisor success. The study also unveils a range of challenges and issues faced by unit trust advisors, which can substantially impede their ability to deliver optimal outcomes. Market volatility emerges as a significant hurdle, with fluctuations in economic conditions and investor sentiment influencing advisors' capacity to achieve consistent sales. Building trust with clients and educating them about unit trust products represent additional challenges that advisors must navigate. By identifying both influencing factors and performance challenges, organizations and the industry at large can identify areas of strength and opportunities for improvement. Addressing the issues faced by unit trust advisors and enhancing their capacity to manage challenges can lead to improved client outcomes and overall success in effectively managing unit trust investments.